A pilot test on the holistic support system for dual career student athletes - Leung, E.; Sum, R.; Cheung, T. F.; Yu, K.; Kwong, A.; Chiu, J. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Background: Dual career athletes who are enrolled in universities face significant demands in both their athletic pursuits and academic commitments. Failing to address their difficulties can lead to a decline in performance in both sports and academics. Purpose: This pilot study aimed to investigate the available support systems for dual career student athletes pursuing higher education in Hong Kong, while identify the key challenges they face. Methods: The study utilized a quantitative research method, employing an online questionnaire distributed to 107 student athletes at Hong Kong National Squad or Junior Squad level pursuing undergraduate studies in a university. The questionnaire gathered data on demographic information, the support measures provided by university and sports associations and the challenges of dual career student athletes. The questionnaire was adapted from Linnér and colleagues (2021) research. Eligibility criteria included: (a) full-time undergraduate students, (b) recipients of sports scholarships provided by the university, and (c) Hong Kong National Squad or Junior Squad members. The data was analyzed using descriptive statistics. Independent t-test was used to calculate between-group effects. Results: A total of 38 student athletes (M: 20; F: 18) were recruited for the study. Among the various learning supports provided by the university, the participants identified the flexible attendance and assignment submission arrangements (25), extension of maximum study period (19), and scholarships (15) as the top three most important supports. Overall, the participants expressed satisfaction with the supports provided by their university, with a mean satisfaction rating of 4.80 out of 6 and a standard deviation of 0.7971. There was no significant difference in satisfaction levels between male and female students regarding the supports provided by the university. Regarding the training supports provided by sports associations, the participants highlighted flexible training attendance (18), sports development advice (13) and scholarships (9) as the top three most important supports. The participants also expressed satisfaction with the supports provided by their sports associations, with a mean satisfaction rating of 4.55 out of 6 and a standard deviation of 0.8870. There was no significant difference in satisfaction levels between male and female students. The major challenges reported by the student-athletes included time management (24), time conflicts between training/competitions and classes/examinations (10) and striving to balance sports and striving to balance sports and academics (8). Conclusion: This study explored the experiences and perceptions of student-athletes regarding the supports provided by university and sports associations, and the challenges they encounter. The findings highlight the need for effective time management strategies and support systems to help student-athletes overcome their challenges.